Sampling method to evaluate Cercospora musae damages of banana leaf - Pereira, Lair Victor; Alves, Élio José; Caldas, Ranulfo Corréa (Pesquisa Agropecuaria Brasileira, 2014)
The present work was carried out in order to establish a sampling method, based upon an adequate number of leaves, their positioning on the plant and also on the ideal number of plants per treatment, to evaluate the damages caused by Cercospora musae Zimm, which causes the sigatoka's disease on banana leaf. The data were obtained from ten plants, by counting the, number of lesions inside an area of 100 cm2, measured with a board template at the base, in the middle, and on the apex of both leaf edges. The percentage of the leaf area affected was obtained by multiplying the number of lesions/pattern by the previously determined lesions of 0.50 cm2. The results showed significant differences with respect to the lesions among leaf positions in the same plant. Ten plants per treatment are sufficient, being the observations based on the leaves in the positions 7, 8 and 9, which were the most representative ones.
Keywords: Musa sp.; Sigatoka's disease; Mycosphaerella musicola